Central Banks and Gold : How Tokyo, London, and New York Shaped the Modern World - Bytheway, Simon James, 1969-; Metzler, Mark, 1957- (Book collections on Project MUSE., 2016)
In recent decades, Tokyo, London, and New York have been the sites of credit bubbles of historically unprecedented magnitude. They have cooperated to construct and preserve towering structures of debt, reshaping relations of power and ownership around the world. In this book, the authors explore how this financialised form of globalism first took shape a century ago, when Tokyo first joined London and New York as a major financial centre.